LEVANTAMIENTO Y MAPEO DE LOS BIENES CULTURALES DE LA PARROQUIA PUNÍN EDUCACIÓN PATRIMONIAL Y MATERIALIDAD - Pilataxi Gordon, Diana Marisol (2020)
The present research addresses the main topic of the survey and mapping the Punín parish's cultural assets: heritage education and materiality. This results from knowing the current status, valuation, and protection of each patrimonial asset of the parish, subsequently to carry out a survey and mapping of these materialities, thereby making thematic maps of the assets that the parish possesses, detailing its main characteristics. In the development of this qualitative research, the techniques and instruments that will be used for data collection: the interview, observation guide, documentary analysis, and the registration of the INPC cards, techniques that will facilitate the work to know the cultural heritage of the Punín parish; the applied methodology will allow knowing the existing cultural assets. The research design is characterized by being qualitative and not experimental; the data that will be obtained during the bibliographic work will be beneficial for the realization of the fieldwork using the different instruments above, based on the geopositioning of cultural heritage assets and materials of the Punín parish. Each one of these assets will be included in a thematic heritage map and the registration of intangible heritage assets in the INPC cards. The maps that will be made with tangible heritage cultural assets will be more didactic and thematic to understand its features better.